Corporate Social Responsibility (CSR) Based on Islamic Social Reporting in an Effort to Increase Company Value: a Literature Review - Saputra, Agung; Rosmanidar, Elyanti; Elyanti (ILTIZAM Journal of Shariah Economics Research, 2023)
This research aims to investigate the concept of Corporate Social Responsibility (CSR) based on Islamic social reporting and its impact on increasing company value. This research is a type of qualitative descriptive research using the literature study method, with the aim of knowing the results of implementing ISR-based Corporate Social Responsibility (CSR) to increase company value. The research results show that the implementation of corporate social responsibility (CSR) is based on Islamic Social Reporting in an effort to increase company value by referring to several core topics discussed in (1) Finance and Investment; (2) Products and services; (3) Employees; (4) Community Involvement; (5) Environment; (6) Corporate Governance, this sixth subject is issued by the Accounting and Audit Organization for Islamic Financial Institutions (AAOIFI).